A RESEARCH AGENDA FOR STRATEGIC MANAGEMENT IN THE 1990s - Lyles, Marjorie A. (Journal of Management Studies, 1990)
ABSTRACTThe importance of thinking strategically is often glossed over when academics try to apply this concept to themselves. This frequently results in research or articles that are not very insightful or useful either to other academics or to practising managers. To overcome this problem and to explore the future needs of the field of strategic management, this article proposes topics for a research agenda for strategic management in the 1990s that is based on the forecast of ‘experts’ in the field.